Testing the relativistic Doppler boost hypothesis for supermassive binary black holes candidates via broad emission line profiles. Issue 3 (6th December 2019) - Song, Zihao; Ge, Junqiang; Lu, Youjun; Ji, Xiang
ABSTRACT: Optical periodicity QSOs found by transient surveys are suggested to be subparsec supermassive binary black holes (BBHs). An intriguing interpretation for the periodicity of some of those QSOs is that the continuum is radiated from the accretion disc associated with the BBH secondary component and modulated by the periodical rotation of the secondary via Doppler-boost effect. Close to edge-on orbital orientation can lead to more significant Doppler-boost effect and thus are preferred for these systems, which is distinct from those normal type-1 QSOs with more or less face-on orientations. Therefore, the profiles of broad lines emitted from these Doppler-modulated systems may be significantly different from other systems that are not Doppler modulated. We investigate the properties of the broad emission lines of optical-periodicity QSOs, including both a sample of QSOs that can be interpreted by the Doppler-modulated effects and a sample that cannot. We find that there is no obvious difference in the profiles and other properties of various (stacked) broad emission lines of these two samples, though a simple broad line region model would suggest significant differences. Our finding raises a challenge to the Doppler boost hypothesis for some of those BBHs candidates with optical periodicity.